The Effect of Capital Structure on Company Performance and the Impact of the Stock Market Value of the Manufacturing Industry Listed on the Indonesia Stock Exchange. - Masno Marjohan; Hadi Supratika (AIBPM Publisher, 2022)
Capital structure decisions are fundamental to the survival of the company. This study is to determine the effect of capital structure on company performance and the impact of stock market value from manufacturing industries listed on the Indonesia stock exchange. Data obtained from the company's annual reports from 2015 - 2019, descriptive analysis with a quantitative approach, with the sampling technique used by 10 companies using the purposive sampling method. As for the analysis tool using Path analysis, these findings reveal that each of the following (1) Debt to Equity Ratio has a negative and insignificant effect on Return on Assets. (2) Asset Growth has no significant positive effect on Return on Asset. (3) Debt to Equity Ratio and Asset Growth together (simultaneously) have no significant effect on Return on Asset (4) Return on Asset has no significant effect on Price Book Value. This study is expected to contribute to the company, improve company performance, and maintain good and efficient working capital so that investors are interested in investing in the company. Future researchers can carry out similar research in small and medium scale industries.Keywords: Performance, Company Survival, Stock Market Value, Capital Structure